541.183.553.62 “STUDIES OF ADSORPTION, KINETICS AND THERMODYNAMICS OF HEAVY METALL IONS ON CLAY ADSORBENTS” - Ibragimov, Tohirbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Including the study investigated the isotherms of adsorption of Zn2⁺ ions in wastewater using newly modified adsorbents. Adsorption properties were analyzed based on Freyndlix, Lengmuyur, Dubinin-Radishkovich, and Temkin isotherm models. Based on the results of the study, it was found that Kaolins modified with Angren-activated kaolin (AFK) and Angren-inactive kaolin (AFMK) have the property of effectively adsorbing zinc ions in urban wastewater. The adsorption capacity of Zn2⁺ ions of synthesized adsorbents has been determined as follows: AFK — 0.151 mg/g; AFMK — 0.162 mg/g. According to adsorption isotherms analysis, the Lengmuyur model best described adsorption processes.